Perbedaan Hasil Belajar Biologi Siswa SMA Peserta Bimbingan Belajar Klasikal dengan Privat di Smart Centre Boyolali Tahun 2016 - Qorina, Nu'ma, Dra. Suparti, M.Si (2017)
Tutoring agency is one of institution Non-formal education. Smart Centre Boyolali is a tutoring agency that has two types of guidance is the guidance of classical tutoring and private tutoring. The purpose of this study to determine differences of biology learning outcomes student senior high school participants in mentoring classical with privet in Smart Centre Boyolali at 2016. This research is ex post facto with a population of high school mentoring students classical and private in the Smart Centre Boyolali and samples of this study were 58 students. Sampling technique used is purposive sampling. The method used is observation, interview, documentation. Data analysis technique used is descriptive analysis and statistical analysis in form of Mann Whitney U Test. Based on the description analysis, that mean (average) high school student learning outcomes participant private tutoring is greater than the mean learning outcomes participant classical tutoring that 87.5 > 86.75. Statistical analysis showed the Sig 0.700 > 0.05, which no significant difference in learning outcomes among high school students participant mentoring classical with participant mentoring privet in the Smart Centre Boyolali. Based on the results of this study concluded that there are no differences in learning outcomes biology students senior high school participant of mentoring classical with privet in with Smart Center Boyolali at 2016.